Severe COVID-19 infection in a kidney transplant recipient treated with lopinavir/ritonavir, hydroxychloroquine and dexamethasone - Satriyo Dwi Suryantoro, - (Open Learning on Enteric Pathogens, 2021)
Severe COVID-19 infection management for a recipient of kidney transplant has debatable prognosis and treatment. We described the case of a COVID-19 infected 70 year old female, previously had renal transplantation in 2017. The patient took immunosuppressive agents as routine drugs for transplant recipient status and received lopinavir/ritonavir, hydroxychloroquine, and dexamethasone daily at the hospitalization. Specific question arises about renal transplant recipients being infected by COVID-19 – whether the infection will get worse compared to those without immunosuppresive agent. In this case, author decided to stop the immunosuppressive agent followed administration of combination lopinavir/ritonavir, hydroxychloroquine, and dexamethasone that gives a good clinical impact change to patient’s condition after once getting worsened and mechanically ventilated. Nevertheless, the assessment of risk and benefit in continuing immunosuppressive drugs is concurrently essential due to the prevention of transplant rejection.